Metabolism plays the key roles in Th cells differentiation - A. Hosseinzadeh; S. Soukhtehzari; M. Ghaedi; R. Mansouri (PAGEPress Publications, 2016)
The increasing rate of autoimmunity in recent decades cannot be related to only genetic instabilities and disorders. Diet can directly influence our health. Studies have shown that there is a relationship between nutritional elements and alteration in the immune system. Among immune cells, the function of T lymphocyte is important in directing immune response. T CD4+ cells lead other immune cells to respond to pathogens by secreting cytokines. HIV+ patients, who have largely lost their T CD4+ cells, are susceptible to opportunistic infections, which do not normally affect healthy people. It seems that the metabolism of T cells is critical for their differentiation and their consequent functions. After activation, T cells need to undergo clonal expansion, which is a high energy- consuming process. Studies have shown that specific metabolites deprivation or their excess supply affects T CD4+cells subsets differentiation. Abnormal induction of subsets of T CD4+ cells causes some autoimmunity reactions and hyper-sensitivity as well, which may result from imbalance of diet uptake. In this mini-review, we describe the findings about fatty acids, glucose, amino acids, and vitamins, which are effective in determining the fates of T CD4+ cells. These findings may help us uncover the role of diet in autoimmune diseases.